Jesus and the Making of the Modern Mind, 1380-1520 (PDF) - Luke Clossey (2024)
For his fifteenth-century followers, Jesus was everywhere – from baptism to bloodcults to bowling. This sweeping and unconventional investigation looks at Jesus across one hundred forty years of social, cultural, and intellectual history. Mystics married him, Renaissance artists painted him in three dimensions, Muslim poets praised his life-giving breath, and Christopher (“Christ-bearing”) Columbus brought the symbol of his cross to the Americas. Beyond the European periphery, this global study follows Jesus across – and sometimes between – religious boundaries, from Greenland to Kongo to China. Amidst this diversity, Jesus and the Making of the Modern Mind, 1380-1520 offers readers sympathetic and immersive insight into the religious realities of its subjects. To this end, this book identifies two perspectives: one uncovers hidden meanings and unexpected connections, while the other restricts Jesus to the space and time of human history. Minds that believed in Jesus, and those that opposed him, made use of both perspectives to make sense of their worlds. This book includes over one hundred images, tables and audio clips.